Renal artery pseudoaneurysm after renal biopsy: case report - Frizon, André; Bello, Rodrigo; Macagnan, Mauricio; Voss, Larissa; Schaffel, Esther (Brazilian Journal of Case Reports, 2024)
Renal artery pseudoaneurysm (RAP) is a rare and potentially serious complication that can occur after renal biopsy procedures. We present the case of a 37-year-old patient who developed RAP after a renal biopsy, presenting signs of hypovolemic shock shortly after the procedure without signs of hematuria. A computed tomography scan of the abdomen was performed which revealed a significant perirenal hematoma and RAP formation. The patient underwent endovascular embolization, which successfully controlled the hemorrhage. After 6 months of evolution, a small degree of renal atrophy was identified, a known complication following embolization. This case report highlights the importance of early recognition and appropriate management of RAP following renal biopsies and provides information on diagnostic and treatment approaches for this uncommon complication.